(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The work was aimed to formulate intrapocket dental films with rate controlling polymers, capable of delivering therapeutic concentrations of doxycycline hyclate (DCH) for a prolonged period and study the antibacterial activity for local action. Intrapocket dental films of DCH were formulated by solvent casting technique using HPMC E15, eudragit RS 100, PEG 400, dibutyl phthalate. The dental films were optimized on basis of physicochemical parameters such as FTIR, DSC, thickness, uniformity of weight, drug content, surface pH, percentage moisture loss, percentage moisture absorption, tensile strength, swelling index, folding endurance, in vitro bioadhesion test, in vitro drug release and in vitro antibacterial activity. FTIR and DSC showed compatibility between the drug and excipients. The formulated films were flexible, smooth, homogenous, non-sticky and revealed acceptable mechanical and physicochemical characteristics (F11 and F12). The films showed sustained in vitro release for 7 d. Kinetic models indicated DCH release from these dental films was best fit towards first-order kinetics. It is concluded that local therapy of periodontitis with the help of DCH loaded HPMC E15 and eudragit RS 100 dental films have a remarkable role. This combination of HPMC E15 and eudragit RS 100 can be used to develop dental films for other drugs.